Modelling modern qualification upgrade courses for teachers-philologists: from demand to implementation - A. Zhindeeva, Elena (2021)
The article is aimed at researching the possibility of introducing the qualifications upgrade courses for teachers-philologists offering them individual practice-oriented development trajectories based on their level of ambition and evaluation of their performance by independent experts. In our research, we relied on the system-activity approach enriched with the personality-oriented approach to the training of language and literature teachers. Methodologically the research was supported by various theoretical and empirical methods including pedagogical observation, analysis, synthesis and abstracting. This paper provides substantiation for introduction in the design practice of qualifications upgrade courses of a modular principle assuming the right of teachers to choose the course content. In the conclusion, it is shown that the qualifications upgrade course consists of a set of practice-oriented materials, which will allow students to independently plan their learning content by selecting individual components of the program. The paper findings have a practical value for modernization of education and for strengthening the competitiveness of a teacher-philologist through the qualifications upgrade courses.